TINJAUAN YURIDIS PEMBATALAN PERJANJIAN PADA MASA PANDEMI COVID-19 DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Marpaung, Stanley; Roida Nababan; August P silaen (Nommensen Journal of Legal Opinion, 2024)
This study aims to review the jurisdiction of the cancellation of the agreement during the Covid-19 pandemic in terms of the Civil Code. The focus. what are the legal consequences of canceling the agreement during the COVID-19 pandemic in terms of the Civil Code and what legal remedies can be taken by those who suffer losses due to the cancellation of the agreement based on the Civil Code. The type of research used in this study is normative legal research that utilizes literature as a data source. The object of research is based on written legal materials by exploring theories, concepts. and the legal and regulatory principles related to this research. The data collection method is the library research method, namely all efforts carried out to obtain information/data related to the problems studied and the data analysis used is qualitative data analysis methods. Based on the results of the study the legal consequences of canceling the agreement during the COVID-19 pandemic in terms of the Civil Code are: (1) Due to a defect of will, error/mistake/error (dawling), fraud (bedrog) and abuse of circumstances (misbruik van de omstandighenden), (2) Legal remedies that can be taken by those who suffer losses due to the cancellation of the agreement based on the Civil Code can be carried out by litigation and non-litigation based on Law no. 30 of 1999, namely by negotiation, consultation, conciliation, mediation can be done through the local court.